The Influence of the Flipped Learning Model on Creative Thinking Ability in the Revolution 4.0 era - Aloisius Harso; Miftachul Amri; Riyanti Susiloningtyas; Henny Sanulita; Hadi Widodo; Tomi Apra Santosa (Universitas Muhammadiyah Enrekang, 2024)
Many applications of flipped learning have a huge impact on students' creative thinking ability in learning. However, no deep conclusions have been found and are still subjective. This study aims to determine the influence of flipped learning to improve students' creative thinking skills in the era of the industrial revolution 4.0. This type of research is a meta-analysis. The research data came from google scholar, Researchgaet, ScienceDirect and ERIC. The inclusion criteria in this study are research from SINTA and Scopus indexed journals; Research must be experimental or quasi-experimental; Research related to flipped learning models on students' creative thinking skills; Research published in 2020-2024; The study must have complete data to calculate the value of effect size; sample size (N) > 25 students. The results of the analysis of 15 journals concluded that there was a significant influence on students' creative thinking ability with a high mean effect size (ES = 1.12) criterion. These findings explain the application of flipped learning effectively helps teachers and students in improving creative thinking skills in the learning process.